2017
DOI: 10.1016/j.geomphys.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

2-capability and 2-nilpotent multiplier of finite dimensional nilpotent Lie algebras

Abstract: Abstract. In the present context, we investigate to obtain some more results about 2-nilpotent multiplier M (2) (L) of a finite dimensional nilpotent Lie algebra L. For instance, we characterize the structure of M (2) (H) when H is a Heisenberg Lie algebra. Moreover, we give some inequalities on dim M (2) (L) to reduce a well known upper bound on 2-nilpotent multiplier as much as possible. Finally, we show that H(m) is 2-capable if and only if m=1.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Salah satu hal yang menarik di sini bahwa aljabar Lie Heisenberg diperumum dapat menjadi pembentuk aljabar Lie Frobenius melalui jumlah langsung dengan split torus-nya [5], dan representasi grup Lie Heisenbergnya dapat direalisasikan dalam quaternionic stage [6]. Disisi lain penelitian tentang struktur aljabar Lie Heisenberg juga telah banyak diteliti khususnya yang berkaitan dengan polynomial Lie [7], struktur aljabar Lie Heisenberg mengenai dispersiveness of invariant sistem affine control [8], struktur dan pengali Schur aljabar Lie Heisenberg [4], dan 2-capability dan 2-nilpotent multiplier pada aljabar Lie Heisenberg [9]. Berbeda dengan penelitian-penelitian sebelumnya, pada penelitian ini dipelajari sifat aljabar Lie Heisenberg diperumum berdimensi 2n + 1.…”
Section: Pendahuluanunclassified
“…Salah satu hal yang menarik di sini bahwa aljabar Lie Heisenberg diperumum dapat menjadi pembentuk aljabar Lie Frobenius melalui jumlah langsung dengan split torus-nya [5], dan representasi grup Lie Heisenbergnya dapat direalisasikan dalam quaternionic stage [6]. Disisi lain penelitian tentang struktur aljabar Lie Heisenberg juga telah banyak diteliti khususnya yang berkaitan dengan polynomial Lie [7], struktur aljabar Lie Heisenberg mengenai dispersiveness of invariant sistem affine control [8], struktur dan pengali Schur aljabar Lie Heisenberg [4], dan 2-capability dan 2-nilpotent multiplier pada aljabar Lie Heisenberg [9]. Berbeda dengan penelitian-penelitian sebelumnya, pada penelitian ini dipelajari sifat aljabar Lie Heisenberg diperumum berdimensi 2n + 1.…”
Section: Pendahuluanunclassified
“…In the context of a representation theory of a Lie group, we can see that the Heisenberg Lie group can be realized in the quaternionic stage (Balachandirin & et al, 2017) and modular representations over a Heisenberg algebras (Szechtman, 2014). Furthermore, the structure of generalization of the Heisenberg Lie algebra were studied in (Cantuba & Merciales, 2020), (Cantuba, 2019), (Souza, 2019), (Niroomand & Johari, 2018), (Nirooman & Parvizi, 2017), and (Liu & et al, 2012).…”
Section: Keywordmentioning
confidence: 99%
“…Recall from [10], a Lie algebra L is said to be 2-capable if L ∼ = H/Z 2 (H) for a Lie algebra H. In the following corollary, we speciy which ones of Lie algebras with 0 ≤ s 2 (L) ≤ 6 are capable.…”
Section: Proofmentioning
confidence: 99%
“…In [10], the second author showed that the dimension of the 2-nilpotent multiplier of an n-dimensional non-abelian nilpotent Lie algebra L with the derived subalgebra of dimension m is bounded by 1 3 (n − m) (n + 2m − 2)(n − m − 1) + 3(m − 1) + 3. Then dim M (2) (L) ≤ 1 3 n(n − 2)(n − 1) + 3 and so we have dim M (2) (L) = 1 3 n(n − 2)(n − 1) + 3 − s 2 (L) for some s 2 (L) ≥ 0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation